Extractive Reaction of Biodiesel Synthesis Using Ethanol as a Solvent : a Conversion Study - Norhartini, Kassim (2012)
Worldwide high demand for energy, uncertainty of petroleum resources and concern about global climatic changes has led to the resurgence in the development of alternative liquid fuels. Ethanol has always been considered a better choice as it reduces the dependence on crude oil and promises cleaner combustion leading to a healthier environment. Developing ethanol as fuel beyond its current role of fuel oxygenate, would require lignocelluloses as a feedstock because of its renewable nature, abundance and low cost. Nevertheless, in most of the studies, methanol was used as the reaction and extraction medium. The use of methanol deviate the purpose of producing renewable energy since methanol is mostly derived from fossil fuel. Therefore in this study, the use of ethanol as the extraction and reaction medium for biodiesel synthesis to produces FAEE was investigated. The objective of this research is to determine the effect varying extraction rate on the biodiesel production by extractive reaction from palm oil using ethanol as a solvent. The experimental procedure to produce biodiesel consist of 2 major experiment which were control experiment and extractive reaction experiment. Operating condition is at 60 ̊C of temperature with molar ratio of ethanol to oil is 6:1 was fixed. The study shows, the extractive rate on the conversion of ethanol in biodiesel synthesis was improved by the extraction system. As a conclusion, ethanol have a better oil extraction property by applying the extractive reaction.